2022
DOI: 10.1007/s00330-021-08374-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of electron-density dual-energy CT in detection of cervical disc herniation in comparison with standard gray-scale CT and virtual non-calcium images

Abstract: Objectives To assess the diagnostic performance of dual-energy CT (DECT) with electron-density (ED) image reconstruction compared with standard CT (SC) and virtual non-calcium (VNCa) image CT reconstruction for detecting cervical disc herniation. Methods This cross-sectional study was approved by the IRB. We enrolled 64 patients (336 intervertebral discs from C2/3 to C7/T1; mean age, 55 years; 17 women and 47 men) who underwent DECT with spectral reconstruction and 3-T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…33 A retrospective study of cervical disc herniation found improved sensitivity using an electron-density DECT technique. 34 Pumberger et al, the first study of DECT collagen imaging of the spine, created virtual collagen maps to help identify disc injury in the setting of thoracic or lumbar vertebral fracture in 67 patients. 22 Comparing our data relative to the literature is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…33 A retrospective study of cervical disc herniation found improved sensitivity using an electron-density DECT technique. 34 Pumberger et al, the first study of DECT collagen imaging of the spine, created virtual collagen maps to help identify disc injury in the setting of thoracic or lumbar vertebral fracture in 67 patients. 22 Comparing our data relative to the literature is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the implementation of DECT, it is possible to use the high spatial resolution of CT and provide good visualization of vertebral discs and ligaments [ 3 , 46 ]. Booz et al reported excellent sensitivity and specificity compared to MRI as the gold standard for disc herniation in the cervical spine and 95% confidence intervals of 91–98% for unenhanced DECT [ 48 , 62 ], which was confirmed by Shim et al in 2022 with sensitivity levels of 94% and specificity of 90% [ 63 ]. In 2022 Koch et al also described excellent sensitivity of 94% and a specificity of 95% compared to MRI in portal venous phase DECT in thoracic disc herniation [ 64 ].…”
Section: Postprocessingmentioning
confidence: 96%
“…In the human musculoskeletal system, reports on the use of EAN and ED maps are sparse. Electron density images improved cervical disc herniation detection and diagnostic confidence of CT [18]. In the human knee, EAN and ED values significantly differed between calcium pyrophosphate depositions and calcium hydroxyapatite in subchondral and trabecular bone [19].…”
Section: Introductionmentioning
confidence: 98%